Developing unique nanoporous titanate structures for biomedical applications: mechanisms, conversion and substitution - Wadge, Matthew D. (2020)
Titanate structures have been of interest in many sectors, including healthcare, due to their ease of manufacture (low processing temperature and simplistic equipment), ion exchange potential to produce multifunctional (bioactive and antibacterial) surfaces, as well as their nanoporosity. However, their use has been limited to only Ti-containing materials due to the specific wet chemical methodology employed. The work presented in this thesis demonstrates one of the first studies to generate gallium-doped titanate structures as a multifunctional surface, specifically to assess their cytocompatibility and antibacterial potential for biomedical applications. Successive wet chemical (5 M NaOH; 60 oC; 24 h), ion exchange (4 mM Ga(NO3)3; 60 oC; 24 h), and heat treatment (700 oC; 1 h) stages were employed on Cp-Ti surfaces. Gallium was shown to be fully incorporated (ca. 9 at.%) into the nanoporous titanate structure, and completely replaced sodium (initial Na content ca. 3 at.%). The heat treatment stage crystallised the amorphous titanate layer, which increased the stability and reduced the maximum level of Ga3+ released (ca. 2.76 vs. 0.68 ppm for pre- and post-heat treated gallium titanate samples, respectively) into DMEM over 7 d. Finally, the heat-treated gallium titanate samples were shown to be cytocompatible, compared to the non-heat-treated samples, which demonstrated a significant (p < 0.0001) reduction compared to the TCP control. Unfortunately, neither gallium titanate samples exhibited robust antibacterial properties against S. aureus. The applicability of titanate structures was furthered in this thesis through the optimisation and characterisation of novel wet chemical (5 M NaOH; 60 oC; 24 h) titanate-converted Ti thin films deposited via DC magnetron sputtering. The films produced were deposited onto 316L SS to function as thin coatings for orthopaedic applications. This was in lieu of the ‘gold standard’ plasma sprayed hydroxyapatite (HA) coatings, due to their inherent shortfalls such as residual internal stresses and long-term delamination. An understanding of the titanate growth mechanism through thickness and oxygen variations was also detailed. Tailorable coating properties (structural, morphological, etc.) were achieved via modification of the sputtering parameters used (target power, substrate biasing, and in situ substrate heating). Graded coating structures from columnar (Tc for the α-Ti (002) plane = 3.39) to more equiaxed (Tc(002) = 1.54) coatings were produced, with their influence on titanate formation being investigated. Equiaxed coatings generated the thickest titanate structures (ca. 1.63 vs. 1.12 μm for columnar grown films) due to a reduction in oblique angle crystal growth because of the decreased surface roughness (Ra: ca. 32.6 vs. 26 nm). This was contrary to the hypothesis that more columnar structures would allow greater NaOH penetration, and hence further conversion. It was also found the titanate structures formed even on 50 nm thick Ti films, as well as oxygen limiting the titanate formation mechanism. Finally, sodium and calcium titanate-converted thin (ca. 500 nm) Ti coatings (both columnar and equiaxed) were applied to Mg substrates to tailor its corrosion resistance for biomedical applications. The columnar calcium titanate coatings performed the best of all the coatings tested compared to Mg in terms of their corrosion resistance (Ecorr = ca. -1.33 vs. -1.49 V; icorr = ca. 0.06 vs. 0.31 mA.cm-2, respectively). The novel method outlined in this thesis has demonstrated consistent production of tailorable nanoporous titanate structures on non-Ti containing materials. Furthermore, the produced titanate structures enabled ion substitution of Ca ions, which have previously only been achieved in titanate structures produced on Ti substrates. The results detailed not only enhances the understanding of the titanate growth mechanism, but also demonstrates the broad applications enabled through this platform technology.